PRODUKTIVITAS LAHAN DAN BIAYA USAHATANI TANAMAN PANGAN DI KABUPATEN GUNUNG KIDUL - Suwarto Suwarto (Muhammadiyah University Press, 2008)
This research aims to investigate land productivity and cost of production of food crops farm in Gunung Kidul. The result of this research found that using labor, fertilizer, and manure increases the land productivity. Similar to, farmers education increases the land productivity. Based on dummy variables, the household labor increases the land productivity. The self-owned land productivity is higher than the rented one belonging to HB, land productivity of forestation department loan is lower than the rented one belonging to HB. Prices of labor, phosphate fertilizer, and organic manure increases the production cost of food crops farm. Based on dummy variables, the production cost of food crops farm LKP rented land is higher than one from other land institution. On the contrary, the cost of production of food crops farmland forestation department loan is lower than one from other land institution.